Age-Related Changes in Suppressor Functions of Human T Cells - Susumu Kishimoto; S Tomino; Hiroaki Mitsuya; Hirokazu Fujiwara (1979)
Abstract Functions of both naturally occurring suppressor and Con A-activated suppressor cels were compared among newborns, young adults, and aged subjects. When T cells were irradiated to remove suppressor activity and added to PWM-stimulated allogeneic B cell cultures, an enhanced Ig production resulted. This irradiation-induced enhancement for IgG production was significantly lower in aged group than in newborns or young adults (p ≦ 0.01). With regard to IgM production, the enhancement was significantly depressed in aged subjects as compared with newborns (p = 0.05). The radiation dose for the generation of T cells capable of exerting the greatest enhancement was between 900 and 1200 rads in both young adults and aged subjects, but as high as 1600 rads in newborns. Furthermore, newborns were shown to be enriched for T suppressor activity by co-culturing of allogeneic PBL with T cells in the presence of PWM as compared with young adults. T cells isolated from young adults, but not from aged subjects, enhanced IgM and IgG production by allogeneic B cells beyond the synergy obtained by control T cells when pretreated with mitomycin and then co-cultured with B cells and PWM. The means of maximal enhancements were significantly greater in young adults than in the aged (p = 0.02 for IgG, p < 0.05 for IgM). The study on the kinetics of generation of Con A-activated suppressor cells revealed that T cells isolated from young adults mediated maximal suppression of Ig production when activated by incubation with Con A for 2 days and added to PWM-stimulated PBL cultures. By contrast, T cells from aged humans required 1 or 2 more days of incubation with Con A to be activated to obtain the maximal suppressor activity. In addition, the means of maximal suppression of IgM and IgG production mediated by Con A-activated T cells were significantly greater in young adults than in the aged (p = 0.02 for IgG and p = 0.05 for IgM). Impaired function of both naturally occurring suppressor and Con A-activated suppressor cells is discussed in relation to altered immunocompetence seen in aged humans.